COST-EFFECTIVENESS ANALYSIS OF THE USE OF NARCOTIC ANALGESICS IN PATIENTS WITH POST-CAESAREAN SECTION AT A MOTHER AND CHILD HOSPITAL IN PANDEGLANGHILD HOSPITAL IN PANDEGLANG - Yusransyah, Yusransyah; Stiani, Sofi Nurmay; Adini, Syilvi Adini; Fauzi, Suci Nurul (Jurnal Farmasi Sains dan Praktis, 2026)
The majority of patients undergoing cesarean section experience moderate to severe pain. To reduce pain after surgery, therapy can be used in the form of administering narcotic analgesics. The selection of the type of narcotic analgesic affects the level of effectiveness of treatment and the costs required. This study aims to identify the most cost-effective narcotic analgesic therapy in post-cesarean section patients. The study was conducted using a non-experimental method using a descriptive approach, as well as prospective data collection through cost analysis and direct interviews with patients using questionnaires. Cost-effectiveness analysis was conducted using the Cost Effectiveness Analysis (CEA) method using ACER and ICER values. The sample was selected by purposive sampling with a total of 90 patients, consisting of 38 patients in the Fentanyl group and 52 patients in the Fentanyl + Morphine group. The results showed that cost efficiency based on the Faces Pain Rating Scale pain scale produced an ACER value of IDR 1,561 for the Fentanyl group and IDR 1,499 for the Fentanyl + Morphine group. Meanwhile, based on the Visual Analogue Scale (VAS) pain scale, the ACER value for the Fentanyl group was IDR 751 while for the Fentanyl + Morphine group it was IDR 3,404. Based on these findings, the most cost-effective narcotic analgesic therapy according to the Faces Pain Rating Scale assessment is the combination of Fentanyl + Morphine, but based on the Visual Analog Scale assessment, the use of Fentanyl is more cost-effective than the combination of Fentanyl + Morphine.